Amelioration of iron overload-induced liver toxicity by a potent antioxidant and iron chelator, Emblica officinalis Gaertn. (July 2015) - Sarkar, Rhitajit; Hazra, Bibhabasu; Mandal, Nripendranath
In liver, the major site of iron storage, iron overload is associated with oxidative damage of protein, lipid, and DNA and causes protein oxidation, lipid peroxidation, and rupture of hepatocytes, leading to cell death. Serum ferritin and liver iron content are the main forecasters of moderate to severe iron overload in the liver. The sequels of excess iron deposition in the liver are fibrosis and enhanced levels of serum enzymes and bilirubin markers. Emblica officinalis (EO) fruit extract was found efficient in lessening intraperitoneally injected iron dextran-induced liver toxicity in Swiss albino mice. Mice administered with different doses of 70% methanol extract of EO (50, 100, and 200 mg kg −1 body weight) showed significant decrease in liver iron, serum ferritin, and serum enzyme levels, along with the decrease in lipid peroxidation, protein oxidation, and collagen content. The activity was further supported by its considerable iron chelation with half-maximal inhibitory concentration of 70.24 ± 2.74 μg ml −1 and the protection on ferrous ion-mediated DNA breakdown with 50% protection ([P]50 ) of 1.04 ± 0.01 μg ml −1 . Simultaneously, the extract effectively induced the antioxidant enzyme levels and also exhibited the potential activity of reductive release of ferritin iron. These findings suggest that the EO extract may be used as a potent drug for the treatment of pathological sequences arisen in the iron overload-induced liver damage.